Research on tribological performance of piston ring/liner conjunction considering non-Gaussian roughness and cavitation. (April 2023) - Prajapati, Deepak K; Ramkumar, P; Katiyar, Jitendra K
The tribological performance of piston ring-cylinder liner conjunction (PRCLC) notably depends on the surface finish of cylinder liner. This study investigates the mixed lubrication condition near dead centres considering non-Gaussian roughness and cavitation. The non-Gaussian flow factors are incorporated in the average Reynold's equation to include the effect of non-Gaussian roughness. Whereas, the Weibull probability distribution function is employed to model the asymmetry in asperity heights. It is found that surfaces with more negative skewness exhibit lower engine total frictional force in the vicinity of the dead centres. No substantial effect of the skewness and surface roughness is observed in the mid-stroke of the piston. It is shown that PRCLC operates in mixed-EHL regime near the dead centres. The lambda ratio is found to increase with an increase in skewness of the rough surface.